ANALISIS KETAHANAN PANGAN MELALUI PEMODELAN USAHA TANI SINGKONG - Machfudz, Masyhuri; Khoiriyah, Nikmatul (Fakultas Ekonomi, UIN Maliki Malang, 2013)
aim this research are i) description analyze of cassava distribution optimalisize and useful analyze ‘berusahatani’ of cassava at Malang regency. The Method by using qualitative description approach. The research result shows that: (i) Malang Regency unreach optimally result because of unbalance. It means still occur over and less of production supply and demand of cassava. (ii) empowering farmer family, by using clear area which get social, economic, healthy and culture advantage. Planting cassava in the clear area rises awareness that using land area well will avoid of useless activity. Beside of that by using clear land can minimalize plant desease cause of rat. According the local society, by that way the rat will feel happy and comforted (‘keslimur’: javanese). These result of research can be recommended that culture of planting cassava is so significant to support of food guard in this country.